Maoberry (Antidesma bunius) ameliorates oxidative stress and inflammation in cardiac tissues of rats fed a high-fat diet - Arunwan Udomkasemsab; Chattraya Ngamlerst; Poom Adisakwattana; Amornrat Aroonnual; Rungsunn Tungtrongchitr; Pattaneeya Prangthip (BMC, 2018)
Abstract Backgound Chronic fat-rich diets consumption is increased risk associated with cardiovascular diseases (CVD). Prevention or reduction the progression of cardiac tissue deterioration could benefit in CVD. This study aimed to examine the effects of maoberry (Antidesma bunius), a antioxidant-rich tropical fruit, supplementation on oxidative stress and inflammation in cardiac tissues of rats fed a high-fat diet (HFD). Methods The male rats orally received HFD with maoberry extract doses of 0.38, 0.76 or 1.52 g/kg or simvastatin (10 mg/kg) for 12 weeks. At the end of the experimental period, the rats were fasted, euthanized and harvested for the hearts. Results Significantly reduced oxidative stress (malondialdehyde levels) and enhanced antioxidant capacity (ferric-reducing activities) in cardiac tissues of the rats were found. Maoberry extract remarkably ameliorated the expressions of genes involved with pro-inflammatory such as the tumor necrosis factor alpha (TNF-α), interleukin-6 (IL-6), vascular cell adhesion molecule-1 (VCAM-1), monocyte chemoattractant protein-1 (MCP-1) and endothelial nitric oxide synthase (eNOS). Conclusions Our findings suggest that maoberry extract has remarkable effects on preventing progression of cardiac tissue deterioration at least through lowering oxidative stress and inflammation.